RESEARCH METHODS IN INTERCULTURAL COMMUNICATION. A PRACTICAL GUIDE - Thuy Linh, Nguyen Thi (VNU Journal of Foreign Studies; Vol 35 No 6DO - 10.25073/2525-2445/vnufs.4484, 2020)
As the latest one in the Wiley Blackwell series “Guides to research methods in language and linguistics”, “Research methods in intercultural communication”, edited by Zhu Hua, is described on their website as “the most comprehensive volume on research methods in intercultural communication research in the last 30 years” (Wiley, 2016). This book is the contributory collection of a global team of experienced scholars and researchers from intercultural communication, anthropology, education, applied linguistics, and communication, explain both established and emerging research methods and analytical tools. It seeks to provide an introduction to the key methodological issues and concerns in the study of Intercultural Communication for students on advanced undergraduate and postgraduate programs in Intercultural Communication, language and linguistics, applied linguistics, TESOL, education, translation, communication studies and other related subjects.